2023
DOI: 10.1021/acs.inorgchem.2c04249
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Photoactivity of Organoarsenic Hybrid Polyoxometalates

Abstract: Organofunctionalization of polyoxometalates (POMs) allows the preparation of hybrid molecular systems with tunable electronic properties. Currently, there are only a handful of approaches that allow for the fine-tuning of POM frontier molecular orbitals in a predictable manner. Herein, we demonstrate a new functionalization method for the Wells−Dawson polyoxotungstate [P 2 W 18 O 62 ] 6− using arylarsonic acids which enables modulation of the redox and photochemical properties. Arylarsonic groups facilitate or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…28 The first examples of organoarsonatecontaining heteropolyoxotungstates, POTs, incorporating one or more heteroatoms in their shells and often able to act as potential polydentate ligands toward oxophilic metal ions, [ 32 Newton et al also recently demonstrated that arylarsonate-POT hybrids display photosensitivity and thus can potentially be used in photocatalysis and photochromic devices. 29 Multidentate [α-H 2 P V 2 W VI 12 O 48 ] 12− phosphotungstates ({P 2 W 12 }, see Figure S1) 33 representing a hexalacunary derivative of the Wells−Dawson polyanion [α-P V 2 W VI 18 O 62 ] 6− , i.e., where six neighboring W VI centers have been removed from the parent structure, constitute a special interest for functionalization due to its high reactivity and ability to bind multiple heterometal ions 34 as well as to oligomerize in dimeric {P 4 W 24 }, 24,35,36 open-shell {P 6 W 36 }, 37,38 cyclic {P 6 W 39 }, and 39 trimeric and wheel-shaped tetrameric {P 8 W 48 } 40 24 We also found that the solutionstable phenylphosphonate-functionalized {P 4 W 24 } dimers exhibit a reactivity that is highly unusual for the nonfunctionalized species, which allows the isolation of previously unknown complexes with {P 4 W 27 } topology, 41,42 able to induce rare trigonal-prismatic coordination geometries for rare-earth ions. 41 Herein, we report on the results of our further investigations on {P 33 and its identity and purity were confirmed by IR spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 The first examples of organoarsonatecontaining heteropolyoxotungstates, POTs, incorporating one or more heteroatoms in their shells and often able to act as potential polydentate ligands toward oxophilic metal ions, [ 32 Newton et al also recently demonstrated that arylarsonate-POT hybrids display photosensitivity and thus can potentially be used in photocatalysis and photochromic devices. 29 Multidentate [α-H 2 P V 2 W VI 12 O 48 ] 12− phosphotungstates ({P 2 W 12 }, see Figure S1) 33 representing a hexalacunary derivative of the Wells−Dawson polyanion [α-P V 2 W VI 18 O 62 ] 6− , i.e., where six neighboring W VI centers have been removed from the parent structure, constitute a special interest for functionalization due to its high reactivity and ability to bind multiple heterometal ions 34 as well as to oligomerize in dimeric {P 4 W 24 }, 24,35,36 open-shell {P 6 W 36 }, 37,38 cyclic {P 6 W 39 }, and 39 trimeric and wheel-shaped tetrameric {P 8 W 48 } 40 24 We also found that the solutionstable phenylphosphonate-functionalized {P 4 W 24 } dimers exhibit a reactivity that is highly unusual for the nonfunctionalized species, which allows the isolation of previously unknown complexes with {P 4 W 27 } topology, 41,42 able to induce rare trigonal-prismatic coordination geometries for rare-earth ions. 41 Herein, we report on the results of our further investigations on {P 33 and its identity and purity were confirmed by IR spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For the last two decades, the integration of various organic ligands, e.g. , triols, , pyridyls, organo­(bis)­phosphonates, , and organoarsonates, , in POMs via exploitation of their active surface oxygen atoms has been actively investigated. Our research in this context is mainly focused on the incorporation of organoarsonate moieties, RAs V O 3 2– , offering a robust {AsO 3 } group able to condense to the metal centers of a polyanion as well as an organic moiety R, which may comprise various active groups (for example, −NH 2 , −OH, −NO 2 , etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] By tailoring the nature of the organic moiety in particular, the resulting hybrid species can demonstrate synergistic properties which can be finely tuned. [26][27][28][29][30] Here, we show how targeted design of a hybrid POM cluster containing Ru-polypyridyl moieties as catalyst units can be employed to enhance the activity and dramatically alter the selectivity of the electroreduction of CO 2 . The new hybrid compound: ( n Bu 4 N) 3 H[(Ru(dmbpy)(ppt)Cl) 2 P 2 W 17 O 57 ] (1) ( n Bu 4 N = tetrabutylammonium, dmbpy = 4,4 0 -dimethyl-2,2 0 -dipyridyl, ppt = 4 0 -(4-phosphonophenyl)-2,2 0 : 6 0 ,2 00 -terpyridine), is shown to be an active species for both CO/H 2 and formic acid (HCOOH) production, where the product distribution can be switched from CO/H 2 to HCOOH by the addition of a weak proton donor due to the pre-association of protons to the reduced POM core.…”
mentioning
confidence: 99%
“…23–25 By tailoring the nature of the organic moiety in particular, the resulting hybrid species can demonstrate synergistic properties which can be finely tuned. 26–30…”
mentioning
confidence: 99%